(untitled) (Tạp chí Y học Cộng đồng, 2026)
DEHEMA is an herbal product developed from the ancient remedy “Tao Hong Si Wu Tang”, clinically prescribed for blood stasis syndrome caused by injury, contusion or surgeries. Objectives: To evaluate the analgesic effects of DEHEMA in experimental animals. Methods: The study was conducted using three animal models: hot plate test, Von Frey test and acetic acid-induced writhing test. Mice were divided into five groups and were orally administered: group 1 distilled water; group 2 paracetamol combined with tramadol; groups 3 diclofenac; group 4 DEHEMA high dose of 48mL/kg b.w./day; group 5 DEHEMA low dose of 24mL/kg b.w./day. Results: The DEHEMA groups showed a tendency in prolonging the heat response time in the hot plate model; prolonging the response time to pain stimuli and increasing force required to elicit pain in Von Frey test; delaying the onset time and reducing the number of writhing in acetic acid-induced writhing model. Conclusions: This study’s findings suggest the potential analgesic effects of DEHEMA in experimental models.